2021
DOI: 10.3390/f12020214
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Carbon, Nitrogen, and Phosphorus Stoichiometry of a Robinia pseudoacacia Plantation on the Loess Hilly Region, China

Abstract: Seasonal variations in stoichiometry are a crucial regulatory mechanism for plant communities that respond to environmental changes. However, the seasonal characteristics of stoichiometry in plants, litter, and soil are poorly understood, especially in plantation ecosystems. Therefore, we explored the seasonal variations of C, N, and P contents and ratios between plants, litter, and soil of a Robinia pseudoacacia plantation on the Loess Plateau in China in 2017. The results indicate that the C, N, P contents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Consistent with previous studies ( Dong et al., 2021 ; Li et al., 2022 ), we found that seasonal variation of the structural substance C concentration was lower than that of N and P concentrations. Nutrient elements (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies ( Dong et al., 2021 ; Li et al., 2022 ), we found that seasonal variation of the structural substance C concentration was lower than that of N and P concentrations. Nutrient elements (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the C, N, and P stoichiometries of plants would also vary with the growing seasons ( Sardans and Peñuelas, 2012 ; Li et al., 2017b ). For instance, leaf N and P concentrations of woody species decreased over the growing seasons, whereas the C:N, C:P, and N:P ratios showed the opposite trend ( Dong et al., 2021 ). Similarly, the leaf N and P concentrations of herbs were significantly higher in the early growth season than in other growing seasons ( Wu et al., 2010 ; Liu et al., 2020 ; Xiong et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the mixed species of N-fixing significantly changed the stoichiometric ratios of the 0-10 cm soil layer (Figure 4), which may have been due to the susceptibility of topsoil layer environmental factors and litter decomposition [29]. Generally, soil C:N is not only a sensitive index of the C and N storage but also the quality of the soil in the forest ecosystem [30,31]. In our experiment, the average C:N ratio was 20.79 in the selected plantations, which was higher than the global average C:N of 14.3 [32].…”
Section: Effect Of Mixed Afforestation On Stoichiometric Ratiosmentioning
confidence: 70%